POLEMIK MARKETING POLITIK ANTARA IMAGE DAN SUBSTANSI - Muhammad Chabibi (Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The use of marketing in the political domain provides an extraordinary polemic not only from the aspect of scientific epistemology, but also from the aspect of the construction of social reality. The current era, contestation or competition among politicians or prospective leaders uses marketing studies in their winning strategies, on the one hand, to connect them with the public in order to know the problems and needs they want.On the other hand, politicians or candidate leaders aim to gain commitment and support from the public voice of what they have offered or promoted. This article tries to analyze how the political marketing polemic exists in electoral democracy and what political marketing science should prioritize between image or substance. This study uses a qualitative method with a literature study approach related to marketing, politics and democracy.